Becoming Workers? Strikes by Hotel and Restaurant Staff in Italy (1902−1923)*. (7th December 2015) - Raspadori, Paolo
Abstract: Working conditions and labour unrest among service employees in the hotel and restaurant sector have, for a long time, have not been at the centre of attention of labour historians, especially in Italy. However, from the late nineteenth century a considerable number of cooks and waiters in Italian cities began to organize in order to improve their working conditions and to create alternative, cost-free forms of employment. From the early twentieth century, the trade unions of the employees of hotels and restaurants (grouped together in a National Federation in 1907) attempted to achieve these goals by means of strikes and demonstrations, some of them remarkably militant. Using a broad range of primary sources and quantitative data, this paper will first describe the characteristics of the working conditions of workers in hotels and restaurants in Italy; second, it will analyse the evolution of organizations, demands, and strike action by these staff from the beginning of the twentieth century to the advent of fascism. Distinguishing two waves of mobilization (1902−1907/1908 and 1919−1920), this paper aims, firstly, to highlight the similarities and differences between union actions by hotel and restaurant employees, on the one hand, and those of other workers on the other. Secondly, it focuses on the ways that the strikes induced serving staff to feel like "real" workers in terms of the outlook and behaviour of industrial workers. Abstract : Paolo Raspadori. Devenir des travailleurs? Grèves du personnel de l'hôtellerie et de la restauration en Italie (1902−1923). Pendant longtemps, les conditions de travail et les conflits de travail des employés du service dans l'hôtellerie et la restauration n'ont pas été au centre de l'attention des historiens du travail, particulièrement en Italie. Cependant, depuis la fin des années 1800, un nombre considérable de cuisiniers et de serveurs dans les villes commencèrent à s'organiser pour améliorer leurs conditions de travail et pour créer des formes alternatives sans frais de placement. Depuis le début des années 1900, les syndicats des employés de l'hôtellerie et de la restauration (groupés dans une Fédération Nationale en 1907) tentèrent d'atteindre ces objectifs par des grèves et des manifestations, dont certaines furent extrêmement militantes. Utilisant une vaste gamme de sources primaires et de données quantitatives, cet article, premièrement, décrira les caractéristiques des conditions de travail des travailleurs dans l'hôtellerie et la restauration en Italie; deuxièmement, il analysera l'évolution des organisations, des revendications et de l'action de grève conduites par ce personnel depuis le début du vingtième siècle jusqu'à la montée du fascisme. Distinguant deux vagues de mobilisation (1902–1907/1908 et 1919−1920), cet article vise d'une part, à souligner les différences et les ressemblances entre des actions syndicales des employés de l'hôtellerie et de la restauration par rapport à celles des travailleurs industriels et ruraux et d'autre part, à se concentrer sur les manières dont les grèves incitèrent les travailleurs à avoir l'impression d'être de "réels" travailleurs en termes de perspective et de comportement de travailleurs industriels. Traduction: Christine Plard Abstract : Paolo Raspadori. Arbeiter werden? Streiks von Beschäftigten des Hotel- und Gastgewerbes in Italien (1902–1923). Die Arbeitsbedingungen und arbeitsbezogenen Proteste von Dienstleistungsangestellten in Hotels und Gaststätten standen lange Zeit nicht im Mittelpunkt der Aufmerksamkeit von Arbeitshistorikern. Dies gilt insbesondere für Italien. Ab Ende des 19. Jahrhunderts begann sich jedoch eine beträchtliche Zahl von Köchen und Kellnern in italienischen Städten zu organisieren, um die eigenen Arbeitsbedingungen zu verbessern und alternative, kostenlose Formen der Arbeitsvermittlung zu schaffen. Zu Beginn des 20. Jahrhunderts versuchten die (ab 1907 in einem landesweiten Verband zusammengeschlossenen) Gewerkschaften der Beschäftigten im Hotel- und Gastgewerbe, diese Ziele durch Streiks und Demonstrationen zu erreichen, die mitunter bemerkenswert militant waren. Der Artikel beschreibt zunächst, unter Verwendung eines breiten Spektrums an Primärquellen und quantitativen Daten, die Arbeitsbedingungen der Beschäftigten im italienischen Hotel- und Gastgewerbe; anschließend wird die Entwicklung der entsprechenden Organisationen, Forderungen und Streiks vom Beginn des 20. Jahrhunderts bis zum Faschismus nachgezeichnet. Dabei werden zwei Mobilisierungswellen unterschieden (1902–1907/08 und 1919−1920). Der Artikel soll zum einen die Gemeinsamkeiten und Unterschiede zwischen den gewerkschaftlichen Aktionen der Hotel- und Gastgewerbeangestellten einerseits und der Industrie- und Landarbeiter andererseits aufzeigen. Zum anderen soll das Augenmerk darauf gerichtet werden, wie die Streiks der Dienstleistungsangestellten dazu beitrugen, dass sie sich als "richtige" Arbeiter zu fühlen begannen, deren Anschauung und Verhalten denen der Industriearbeiter ähnelten. Übersetzung: Max Henninger Abstract : Paolo Raspadori. ¿Convirtiéndose en trabajadores? El movimiento huelguístico del personal de hoteles y restaurantes en Italia (1902−1923) Durante largo tiempo las condiciones de trabajo y la conflictividad laboral de los empleados en el servicio de hoteles y restaurantes no han sido objeto de atención por parte de los historiadores del trabajo, especialmente en Italia. Sin embargo, desde finales del ochocientos observamos que un considerable número de cocineros y camareros italianos comenzaron a organizarse en las ciudades con el objetivo de mejorar sus condiciones laborales y de idear formas alternativas de colocación laboral que no implicaran coste alguno para ellos. Desde los primeros años del siglo XX, las organizaciones sindicales de los empleados de hoteles y restaurantes (agrupados de forma conjunta en el seno de una Federación Nacional a partir de 1907) intentaron alcanzar sus objetivos mediante la convocatoria de huelgas y manifestaciones, algunas de las cuales destacan por su intensa combatividad. Contando con un amplio abanico de fuentes primarias y de datos cuantitativos este artículo describirá, en primer lugar, las características principales de las condiciones laborales de los trabajadores de hoteles y restaurantes en Italia. Posteriormente pasará a analizar la evolución de las organizaciones, sus reivindicaciones y las acciones de lucha emprendidas por este tipo de empleados desde los inicios del novecientos hasta el advenimiento del régimen fascista. Distinguiendo dos olas de movilización (1902−1907/1908 and 1919−1920) este artículo permite, en primer lugar, resaltar las similitudes y diferencias entre las acciones sindicales de los trabajadores de hoteles y restaurantes comparándolas con aquellas desarrolladas por trabajadores en el ámbito rural e industrial; por otro lado, el texto también permitirá analizar en la manera en que las huelgas inducían al personal de servicio sentirse como trabajadores "de verdad", es decir teniendo perspectivas y actitudes semejantes a las de obreros industriales. Traducción: Vicent Sanz Rozalén